Novel bi-layer coatings for the protection and functionalisation of magnesium-based medical alloys - Wilson, Jonathan M. A. (2024)
Bioresorbable biomaterials represent a revolutionary class of materials in the field of biomedical engineering, offering solutions for various medical applications. Unlike traditional permanent implants, bioresorbable biomaterials are designed to degrade gradually within the body over time, eventually being absorbed and assimilated into the surrounding tissues without the need for surgical removal. Magnesium (Mg) and its alloys are promising candidates for these applications due to their mechanical properties being similar to bone and the biological acceptance in the human body. However, their rapid degradation times are currently not practical for a vast array of clinical applications and as such a way to reduce the corrosion rate or delay the onset of Mg corrosion must be developed.